Feasibility Study of Geopolymer Binder from Terracotta Roof Tile Waste. (2016) - Usha, S.; Nair, Deepa G.; Vishnudas, Subha
Abstract: Geopolymers are amorphous to semi crystalline polymeric products formed by the alkali activation of alumino-silicate materials with alkaline silicate solution at ambient or slightly elevated temperatures, which can be used as alternative to ordinary cement. In this paper, the feasibility of geopolymer binder from terracotta roof tile waste was investigated by varying different parameters like concentration of sodium hydroxide, proportion of sodium silicate to sodium hydroxide solution, alkaline activator to binder ratio and elevated temperature curing. Strength characteristics of geopolymer mortars at 7 and 28 days were investigated and SEM analysis was conducted for establishing the feasibility of roof tile powder waste as a potential source of geopolymer.